In service of two masters : the missionaries of Ocopa, indigenous resistance, and Spanish governance in Bourbon Peru - Jones, Cameron D. (Stanford scholarship online., 2019)
By the early 1700s, the vast scale of Spanish empire led crown authorities to rely on local institutions to carry out their political agenda, including religious orders like the Franciscan mission of Santa Rosa de Ocopa in the Peruvian Amazon. This text follows the Ocopa missions throughout the eighteenth and early nineteenth centuries, a period marked by events such as the indigenous Juan Santos Atahualpa Rebellion and the 1746 Lima earthquake.